(untitled) (Journal of Philosophy, Culture and Political Science, 2019)
This report deals with ethnoculture of Turk people in the context of dialogue between the Eart and the West. The comparavistic analysis of response of different ethnocultures to westernization is given and the idea of careful atlitute to cultural heritage is indelined as basic trait of maturity of the national idea. Critical analysic of negative trends related to cultural luritage of Turk people is given. Furthermore, the tendencies of the modern common to all mankind culture were analyzed, and among them the interaction of civilizations is allotted a basic typical line of humankind development. Author gives the typology of world cultures using modern scientifi c methodology and provides new arguments, which refute «europe-centristic» directions of some culture-philosophers. Keywords: westernization, super civilization of Islam, culture of Turkic peoples, East and West, tolerance.